RESPON PERTUMBUHAN DAN HASIL TANAMAN CAISIM (Brassica Juncea L.) PADA SISTEM HIDROPONIK BERBEDA - Isnaeni, Selvy; Nasrudin (Jurnal Agro Wiralodra, 2022)
Vegetable is the most widely cultivated commodities by farmers and community. The mustard is one of commodity that consumed and favored for human. Hydroponics is cultivated system that known accelerate the harvest period of vegetable crops. Hydroponics system have various types such as nutrient film technique, floating rafts, axis hydroponics, drip irrigation, aeroponics, and other hydroponics system. Hydroponics technique have a different effect to plant growth. The aims of this study to determine response of the growth and yield of mustard with the different hydroponics system. The study conducted on August to September 2021 in screenhouse Universitas Perjuangan Tasikmalaya, Tasikmalaya city. The study used completely randomized design using mustard with three treatments, including NFT, floating rafts, and aeroponics with three times. The results showed that the plant height of mustard on 3, 4, 5 weeks after planting was significantly different, the number of leaves on 4 and 5 weeks after planting 11.33 better than other treatment, and leaf area of mustard planted in NTF system and floating rafts were not significantly different 152.33 and 133.33 cm. The mustard planted using floating rafts system had longest roots 72.15 cm. The fresh and dry weight of mustard on NFT system much better than other treatments 134.2 g and 9.60 g.